Identification of Proteins Associated with Multilamellar Bodies Produced by Dictyostelium discoideum - Denoncourt, Alix M.; Paquet, Valérie E.; Sedighi, Ahmadreza; Charette, Steve J. (PLOS ONE, 2016)
Dictyostelium discoideum amoebae produce and secrete multilamellar bodies (MLBs) when fed digestible bacteria. The aim of the present study was to elucidate the proteic content of MLBs. The lipid composition of MLBs is mainly amoebal in origin, suggesting that MLB formation is a protozoa-driven process that could play a significant role in amoebal physiology. We identified four major proteins on purified MLBs using mass spectrometry in order to better understand the molecular mechanisms governing MLB formation and, eventually, to elucidate the true function of MLBs. These proteins were SctA, PhoPQ, PonC and a protein containing a cytidine/deoxycytidylate deaminase (CDD) zinc-binding region. SctA is a component of pycnosomes, which are membranous materials that are continuously secreted by amoebae. The presence of SctA on MLBs was confirmed by immunofluorescence and Western blotting using a specific anti-SctA antibody. The CDD protein may be one of the proteins recognized by the H36 antibody, which was used as a MLB marker in a previous study. The function of the CDD protein is unknown. Immunofluorescence and flow cytometric analyses confirmed that the H36 antibody is a better marker of MLBs than the anti-SctA antibody. This study is an additional step to elucidate the potential role of MLBs and revealed that only a small set of proteins appeared to be present on MLBs.